2020
DOI: 10.1590/0001-3765202020181147
|View full text |Cite
|
Sign up to set email alerts
|

Activation of SOD-3 is involved in the antioxidant effect of a new class of β-aryl-chalcogenium azide compounds in Caenorhabditis elegans

Abstract: Organic selenium, tellurium and sulfur compounds have been studied due to their pharmacological properties. For instance, the β-aryl-chalcogenium azide compounds have demonstrated antitumoral action in vitro. However, yet no pharmacological actions of this class of compounds were determined in vivo.Caenorhabditis elegans is a nematode that presents innumerable advantages in relation to mammalian models, such as having a small and transparent body, which allows the visualization of its internal anatomy, besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…In this study, both genetic and mutant C. elegans con rmed that quercetin almost does not regulate lifespan extension through DR pathway. This nding was consistent with research by Yang, who reported that otophylloside B prolongs its useful life by regulating the IIS pathway without DR (Motta et al 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, both genetic and mutant C. elegans con rmed that quercetin almost does not regulate lifespan extension through DR pathway. This nding was consistent with research by Yang, who reported that otophylloside B prolongs its useful life by regulating the IIS pathway without DR (Motta et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Zhi et al 2017). SOD and CAT are essential antioxidant enzymes that reduce oxidative damage by converting superoxide to hydrogen peroxide and water, thus preventing lipid peroxidation(Motta et al 2020;Padmaja et al 1993…”
mentioning
confidence: 99%
“…The expression of SOD-3::GFP was determined as described by Motta et al [ 25 ]. Six to eight adult nematodes were placed on agar cover slides containing 2% agarose solution, and 3–5 μL 0.2 mM levamisole solution was added to paralyze them.…”
Section: Methodsmentioning
confidence: 99%
“…Hsp-16.2 is a heat stress-inducible gene [ 33 ] encoding a small HSP that enhances heat stress tolerance in nematodes and maintains protein homeostasis. Sod-3 is an oxidative stress-inducible gene [ 34 ] encoding superoxide dismutase. It can improve nematode resilience by counteracting free radical damage to the organism.…”
Section: Discussionmentioning
confidence: 99%